2022
DOI: 10.3390/agriculture12091318
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the PIN Auxin Transporter Gene Family in Zanthoxylum armatum DC

Abstract: PIN-formed (PIN) proteins are important auxin carriers that participate in the polar distribution of auxin in plants. In this study, 16 ZaPIN genes were identified from the whole genome of Zanthoxylum armatum DC. The physicochemical properties and structure of PIN proteins were determined, and the gene sequences and promoter regions were analyzed to identify cis-acting elements and conserved motifs. The transcript profiles of ZaPIN genes in different tissues and in response to auxin and gibberellin treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Furthermore, the secondary structure prediction of these proteins demonstrated that all PbPINs are composed of α-helices, extended chains, β-sheets, and random coils. The αhelices and random coils represent the major secondary structural elements of the PbPINs, consistent with observations in bamboo pepper [33]. Tertiary structure prediction indicated a high similarity in 3D structure among proteins from different categories, except for PbPIN7, PbPIN9, and PbPIN12.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, the secondary structure prediction of these proteins demonstrated that all PbPINs are composed of α-helices, extended chains, β-sheets, and random coils. The αhelices and random coils represent the major secondary structural elements of the PbPINs, consistent with observations in bamboo pepper [33]. Tertiary structure prediction indicated a high similarity in 3D structure among proteins from different categories, except for PbPIN7, PbPIN9, and PbPIN12.…”
Section: Discussionsupporting
confidence: 84%
“…Analysis of the physicochemical properties of these proteins revealed that, with the exception of PbPIN9, the theoretical isoelectric points (pI) of the remaining 12 PIN gene family members were all above seven. The analysis of physical and chemical properties showed that most of the PbPIN genes were alkaline amino acids, and each member contained the conserved domain Men_Trans (PF03547) in P. bournei, with consistent results in other plant species such as bamboo pepper [33] and soybean [40]. Moreover, PbPIN7, PbPIN9, and PbPIN12 exhibited relatively shorter amino acid sequences, likely contributing to structural, functional, and property distinctions.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The expression levels (FPKM) of eight different tissues of tea plant (roots, mature leaves, stems, flowers, young leaves, old leaves, terminal buds, and fruits) and the expression levels of tea plant under cold stress were downloaded from the tea plant database (http://tpdb.shengxin.ren/ accessed on 4 September 2022) [40]. The expression levels (FPKM) were calculated with log2 (FPKM + 1) [55] and visualized with TBtools software version 0.665 [41].…”
Section: Differences In the Expression Of Cserf Gene Family Membersmentioning
confidence: 99%